Protection of the Rights of Women Workers in the Industrial Sector (Studies on Developing Countries) - Gaeldeba Garaika (LEGAL BRIEF, 2021)
Women workers contribute in enhancing national development. Therefore, the proper fulfillment of the rights of women workers in industrialism sectors must receives special attention. The rights of women worker’s implementation still found alot of irregularities, this literature aims to know the fulfillment of women worker’s rights by the company to complete their needs. The implementation of the fulfillment on the rights of women workers is an obligation that should be endeavored to guarantee their rights.